Effectiveness of Digital Education in Improving Knowledge of Anxiety and Depression Disorders in Adolescents - Wulandari, Nunung; Kartini, Apoina; Purnami, Cahya Tri (Jurnal Locus Penelitian dan Pengabdian, 2025)
Background: Mental health disorders among adolescents are a growing global concern. Adolescents are in a transitional phase that makes them vulnerable to emotional, social, and academic pressures. Mental health education serves as a promising promotive and preventive effort to reduce the prevalence of mental health issues in this age group. This article aims to review the influence of mental health education on reducing the incidence of mental disorders among adolescents based on recent studies. Method: This quantitative study used a pre-experimental design with a one group pretest-posttest approach. A total of 50 adolescents were selected through purposive sampling. Data were collected using a questionnaire assessing knowledge of mental health before and after the intervention. Data were analyzed using the Wilcoxon test. Results: The results showed a significant difference in adolescents’ knowledge levels before and after the mental health education (p-value < 0.05). This indicates that the educational intervention effectively enhanced their understanding of mental health. Conclusion: Mental health education is effective in improving adolescents’ knowledge about the importance of maintaining mental health and recognizing early symptoms of mental disorders.